Pengaruh Strategi Komunikasi Marketing dalam Menarik Minat Mahasiswa Baru di Trisakti School of Multimedia melalui Media Sosial - Budiman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2023)
The communication strategy allows communication actions to be carried out for communication targets designed as change targets. Whereas in the marketing communication strategy the main target is Ï”irst, how to make people aware that they need a product, service or value and if attention has been built, then the most important target is that people are loyal to buy the product, service or value (Bungin, 2015: 62 ). The research method used is the Qualitative Research Method, where information about Marketing Communication Strategies using Social Media is discussed by interviewing new students who have graduated as students and the new student admission team committee. While the data collection techniques used in addition to interviews also carried out literature studies and observational studies. Interviews were conducted with the Head of the New Student Admissions Committee and 10 new students. Primary data were obtained from students who were registered as Trisakti Multimedia School students. The purpose of this research is to become input for agencies that marketing communication strategies are more accurate and responsive in processing data from active users. On Social Media paid accounts (ads) are needed to expand reach and create a time schedule for processing data and daily or weekly and monthly reports.